An Iodine Quantum Dots Based Rechargeable Sodium–Iodine Battery. Issue 3 (24th October 2016) - Gong, Decai; Wang, Bin; Zhu, Jingyi; Podila, Ramakrishna; Rao, Apparao M.; Yu, Xinzhi; Xu, Zhi; Lu, Bingan
Abstract : Rechargeable sodium–iodine batteries represent a promising scalable electrochemical energy storage alternative as sodium and iodine are both low cost and widely abundant elements. Here, the authors demonstrate a rechargeable sodium–iodine battery that employs free‐standing iodine quantum dots (IQDs) decorated reduced graphene oxide (IQDs@RGO) as the cathode. Consistent with the density functional theory the authors find the Na + ions to intercalate into the I unit cell forming stable NaI, and the battery exhibits high capacity, outstanding cycle stability (with a reversible specific capacity of 141 mA h g −1 after 500 cycles at current density of 100 mA g −1 ), and high rate performance (170, 146, 127, 112, and 95 mA h g −1 at current densities of 100, 200, 400, 600, and 1000 mA g −1, respectively). The reversible reactions, I2 /I3 − and I3 − /I − redox couples on insertion of Na + ions, are confirmed via in situ Raman spectroscopy. Notably, even after 500 cycles the morphology and structure of the IQDs exhibit no noticeable change implying their use as a stable cathode material for sodium–iodine batteries. Moreover, the IQDs based flexible full‐cells also exhibit high capacity and long cycle life (the capacity with 123 mA h g −1 at current density of 100 mA g −1 after 100 cycles). Abstract : A rechargeable sodium–iodine battery that employs free‐standing iodine quantum dots decorated with reduced graphene oxide paper as the cathode is presented. Consistent with density functional theory, the Na + ions intercalate into the iodine unit cell forming stable NaI. The battery exhibits high capacity, outstanding cycle stability, and high rate performance that are suitable for practical applications.